Manajemen Sumber Daya Perawat Gawat Darurat pada Masa Pandemi COVID-19 di Ruang Instalasi Gawat Darurat Rumah Sakit Tipe C Medan - Reni Asmara Ariga; Ritha F. Dalimunthe (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2021)
The increase of COVID-19 patients led to an increase in the referral hospitals needed. The referral hospital must have eligibility. The quality of a hospital was determined by the services provided and human resources, there are nurse resources. Effective management was needed in dealing with COVID-19 patients. The purpose of this research to identify the implementation of emergency nurse resource management during a pandemic. The design of this research was quantitative descriptive with a cross-sectional approach which was implemented at Type C Hospital Medan City in March 2021. This research using a total sampling technique, there are 24 respondents. This research used a nurse resource management questionnaire which consists of seven aspects in google form which contains closed and open questions. Data was carried out by descriptive statistical analysis using computer applications. The majority of emergency nurses' resource management aspects in the Emergency Room of Type C Hospital in Medan are not good. Of the seven aspects of assessment, 35% of nurses said it was good, the remaining 65% of nurses said it was not good. Based on the range of satisfaction, the results showed that the management of emergency nurse resources at the Type C Hospital in Medan was not satisfactory. The conclusion is the management of emergency nurse resources was needed because it's effective in handling patients during the COVID-19 pandemic and improving the quality of nurses as a human resource owned by the hospital. Good and quality human resources can increase the competitive value of the hospital.